Mamdouh Odwan’s Styles of poetic intertextuality - Hasan, Muhammad; Ali, Muhammad (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
. This research aims to identify Mamdouh Odwan’s Styles of poetic intertextuality , depending on a first reading of concept of " intertextuality" and its role in providing the process of creativity with traditional expressions that lead the modern text to a level of interacting with other texts. This interaction, furthermore, is denoted via the duality of connection and disconnection sometimes based on copying and following ancient poetic texts and neglecting or even negating them other times. The poetic intertextuality in Odwan’s is crystallized in three styles : connotation by which the poet retains the morphological structure of old poems, relatively ; reference through a word or a sentence of old poem and finally allusion that depends on symbolism in achieving intertextuality with old poetry. This paper will approach the aesthetics of those styles and their sub-divisions in order to reach results that show the effect of poetic intertextuality on making the modern poem open to ancient poetic heritage as well as employing it in a modern visionary context.